CD177 Expression and Inflammation Grade in Helicobacter pylori-Infected Wild-Type and CD177-/- C57BL/6 Mice - Xing-Tang Yang; Zhi-Jun Wang (Analytical Cellular Pathology)
This study was undertaken to further investigate the CD177 expression in Helicobacter pylori- (Hp-) infected wild-type and CD177-/- C57BL/6 mice, which may be helpful to elucidate the relationship between CD177 and Hp-related gastritis. 20 WT mice were randomly assigned into the Hpss1 WT group (n=10) and Hp49503 WT group (n=10); 20 KO mice were randomly assigned into the Hpss1 KO group (n=10) and Hp49503 KO group (n=10). The remaining mice served as controls. Mice in the HpSS1 groups and Hp49503 groups were independently infected with corresponding strains. Results showed that the Hp colonization score was related to the grade of mucosal inflammation (P<0.05). The inflammation grade was comparable between the HpSS1 group and Hp49503 group as well as between the WT group and KO group. In addition, the Hp colonization score was related to the CD177 expression score (P<0.05). The CD177 expression in the Hp colonization group was higher than that in the non-Hp colonization group (P<0.05). CD177 expression was positively related to the inflammation grade (P<0.01). In conclusion, CD177 expression was similar between HP49503- and HPss1-infected WT C57BL/6 mice, and CD177 expression was undetectable in CD177-/- mice. CD177 expression in the gastric mucosa increases with the elevation of inflammation grade. In Hp-infected mice, the inflammation grade had no relationship with the type of Hp strain and the CD177 expression, but the mucosal inflammation score in Hp-infected mice was higher than that in non-Hp infected mice.